2021
DOI: 10.3390/molecules26144361
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perbutyrylated Glucose Derivatives of (–)-Epigallocatechin-3-Gallate Inhibit Cancer Cells Proliferation by Decreasing Phosphorylation of the EGFR: Synthesis, Cytotoxicity, and Molecular Docking

Abstract: Lung cancer is one of the most commonly occurring cancer mortality worldwide. The epidermal growth factor receptor (EGFR) plays an important role in cellular functions and has become the new promising target. Natural products and their derivatives with various structures, unique biological activities, and specific selectivity have served as lead compounds for EGFR. D-glucose and EGCG were used as starting materials. A series of glucoside derivatives of EGCG (7–12) were synthesized and evaluated for their in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Insertion of a specific chain of chemical groups into the molecule of EGCG should protect the reactive hydroxyl groups of EGCG and thereby increase the stability, improve the interaction of EGCG with lipid membranes, and to enhance cellular absorption [ 245 ]. Favorable results have been obtained from methyl-protected EGCG [ 246 ], EGCG monoester derivatives [ 247 , 248 ], alkyl-analogues [ 245 , 249 ], and glycoconjugates [ 250 , 251 ].…”
Section: Advanced Egcg Delivery Formsmentioning
confidence: 99%
“…Insertion of a specific chain of chemical groups into the molecule of EGCG should protect the reactive hydroxyl groups of EGCG and thereby increase the stability, improve the interaction of EGCG with lipid membranes, and to enhance cellular absorption [ 245 ]. Favorable results have been obtained from methyl-protected EGCG [ 246 ], EGCG monoester derivatives [ 247 , 248 ], alkyl-analogues [ 245 , 249 ], and glycoconjugates [ 250 , 251 ].…”
Section: Advanced Egcg Delivery Formsmentioning
confidence: 99%
“…Further studies with high level of evidence are needed to investigate the long-term efficacy and safety of oral administration of EGCG in lung cancer patients. In addition, some studies also revealed that the derivates of EGCG also exert anti-lung cancer activity ( 25 , 80 , 81 ). The anti-lung cancer activity of these derivates needs to be investigated by further studies.…”
Section: Discussionmentioning
confidence: 99%